High-efficiency ultrasound generation excited by an annular distributed Ho:YAG laser with 2.09 µm in carbon fiber reinforced plastics. (February 2023) - Dai, Tongyu; Fan, Jiawei; Wu, Jiaze; Wu, Yuechu; Zhang, Ye
Highlights: High efficiency laser ultrasound of carbon fiber reinforced plastics is developed based on an annular distributed laser excitation source with wavelength of 2.09 µm. The maximum ultrasound signal amplitude higher than 280 mV was realized. Abstract: In this paper, we demonstrate a high-efficiency laser ultrasound in carbon-fiber-reinforced plastics (CFRP) by means of excitation laser spatial distribution modulation. The maximum ultrasound signal amplitude of about 286 mV was achieved by directing an annular laser with wavelength of 2090 nm, energy of 2.5 mJ and pulse width of 16 ns onto CFRP samples. The ultrasonic signal amplitude excited by annular laser is more than one times higher than that by typical Gaussian laser under the same conditions. Also, for CFRP laser ultrasound excited by annular laser, the intensity of ultrasound increased in different frequency components as a whole with increasement of laser energy density. The results indicated that it is an effective technical way to improve photo-acoustic efficiency and amplitude of the ultrasonic signal by shaping 2 μm region excited laser spatial distribution into annular type in the CFRP laser ultrasound.